Bouncing bones—ancient wisdom meets modern science in a new take on locomotion - Levin, Stephen M.; Lowell de Solórzano, Susan (Frontiers in Physiology, 2024)
Recognizing that conventional understanding of animal and human locomotion is based on a dated and reductionist machine modeling of organisms, we set out to create a theory of locomotion by reasoning from first principles. We center on the constraints necessitated by 1) the 2nd law of thermodynamics, 2) the theory of evolution, 3) a systems science view of organisms, and 4) the laws of motion, but we also look for compatibility these constraints might find in emerging areas of scientific inquiry (ecological psychology, processual biology, soft matter, biotensegrity), and in the wisdom embedded in various movement traditions and ancient philosophy. Applying and synthesizing these, we propose an updated “bouncing bones” (BB) model for walking and running, which corresponds with maximum efficiency and conservation of energy.